Pengelolaan Penerimaan Peserta Didik Baru Berbasis Gerakan Transisi Paud Ke SD Yang Menyenangkan Di SD Negeri 48 Dan 58 Lubuklinggau - Dwi Kesuma, Novita; Somantri , Manap; Connie (UNIVERSITAS BENGKULU, 2024)
The purpose of the study is to describe the conditions: the admission system for new students, the implementation of the introduction period to the school environment and the placement of new students at SD Negeri 48 and 58 Lubuklinggau. The research uses a descriptive qualitative method through data collection techniques in the form of interviews, observations, and documentation. The research subjects are principals, teachers and parents of students. The results of the study showed; The PPDB system has eliminated the calistung test, the accuracy of schools determining the path and quota of study groups and the implementation of an integrated web in the registration process. SD Negeri 48 Lubuklinggau has not yet socialized the flow, requirements and guidelines of PPDB through various media; In MPLS, there is minimal active participation of parents/guardians; The placement of students in the classroom uses an integration function (age, gender or registration order).